(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Social isolation is characterised by a lack of meaningful social connections and a reduced sense of belonging in society. In the digital age, young people increasingly use online platforms for communication, which affects their social well-being. This study explores the relationship between social isolation and digital behavior among undergraduate management students, focusing on social media use, preference for digital communication, engagement in online learning, and screen time. Employing a quantitative research design, data was collected through a structured questionnaire. The analysis revealed mixed results regarding the impact of digital behaviours on social isolation. While social media use, digital communication preferences, and online learning engagement did not significantly influence social isolation, increased screen time was linked to lower levels of social isolation. This suggests that moderate, intentional digital engagement might enhance social connectedness rather than detract from it. Regression analysis corroborated the finding that most digital engagements do not significantly predict social isolation, whereas screen time notably affects students’ social experiences. The study highlights the importance of balancing online and offline interactions to foster healthy relationships. Participants indicated that structured screen use can positively impact social well-being by facilitating communication and social support. The findings underscore significant implications for educators, policymakers, and mental health professionals in crafting interventions that promote healthy digital practices and strengthen social connections in digital educational settings.